The Book Business - Shatzkin, Mike; Riger, Robert (Tantor Media, Inc., 2019)
Many of us read books every day, either electronically or in print. We remember the books that shaped our ideas about the world as children, go back to favorite books year after year, give or lend books to loved ones and friends to share the stories we've loved especially, and discuss important books with fellow readers in book clubs and online communities. But for all the ways books influence us, teach us, challenge us, and connect us, many of us remain in the dark as to where they come from and how the mysterious world of publishing truly works. How are books created and how do they get to readers? The Book Business: What Everyone Needs to Know® introduces those outside the industry to the world of book publishing. Covering everything from the beginnings of modern book publishing early in the twentieth century to the current concerns over the alleged death of print, digital reading, and the rise of Amazon, Mike Shatzkin and Robert Paris Riger provide a succinct and insightful survey of the industry in an accessible question-and-answer format. The authors, veterans of "trade publishing," or the branch of the business that puts books in our hands through libraries or bookstores, answer questions from the basic to the cutting-edge, providing a guide for curious beginners and outsiders.
Online resource; Title from title page (viewed May 31, 2019)
Keywords: Publishers and publishing -- United States; Booksellers and bookselling -- United States; Book industries and trade -- United States; Livres; Industrie; États-Unis; Book industries and trade; Booksellers and bookselling; Publishers and publishing; United States; Downloadable audio books; Audiobooks; Livres audio